VITAMIN METABOLISM DISORDERS - P. F. Litvitskii ("Paediatrician" Publishers LLC, 2014)
The reasons and conditions, types, key links of mechanisms of the vitamin metabolism disorders, clinical manifestations of the separate hypo-, hyper- and dysvitaminosis, their pathogenesis are discussed in the lecture.